Functional outcomes and quality of life after total laryngectomy with noncircumferential radial forearm free tissue transfer. Issue 11 (24th August 2017) - Graville, Donna J.; Palmer, Andrew D.; Chambers, Christine M.; Ottenstein, Lauren; Whalen, Breanne; Andersen, Peter E.; Wax, Mark K.; Cohen, James I.
Abstract: Background: The purpose of this study was to compare long‐term functional and quality of life (QOL) outcomes after total laryngectomy with primary closure and those who underwent reconstruction with noncircumferential radial free forearm tissue transfer (RFFTT). Methods: Sixty‐seven patients were identified by chart review and underwent long‐term follow‐up using QOL surveys and standardized interviews. Results: The RFFTT group had significantly higher rates of chemotherapy, gastric tube (G‐tube) at surgery, and postoperative stricture. At follow‐up, most patients (88%) had a tracheoesophageal prosthesis (TEP) and were using it as their primary communication method. Diet and swallowing outcomes were comparable and no one had a G‐tube. Device life and TEP complications did not differ significantly. Only voice‐related QOL differed significantly between the RFFTT group and those who had undergone total laryngectomy without adjuvant treatment. Conclusion: Despite more extensive treatment, the reconstructed group achieved comparable outcomes to those who had undergone total laryngectomy with adjuvant treatment.